2017
DOI: 10.1002/adfm.201604619
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose Nanocrystal Inks for 3D Printing of Textured Cellular Architectures

Abstract: 3D printing of renewable building blocks like cellulose nanocrystals offers an attractive pathway for fabricating sustainable structures. Here, viscoelastic inks composed of anisotropic cellulose nanocrystals (CNC) that enable patterning of 3D objects by direct ink writing are designed and formulated. These concentrated inks are composed of CNC particles suspended in either water or a photopolymerizable monomer solution. The shear-induced alignment of these anisotropic building blocks during printing is quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
448
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 513 publications
(466 citation statements)
references
References 29 publications
(36 reference statements)
18
448
0
Order By: Relevance
“…[1][2][3] Representative sustainable nanocellulose materials like cellulose nanofibers (CNFs) and cellulose nanocrystals (CNCs) have been used as primary constituent materials for additive manufacturing. [7,8] Specially, conductive cellulose inks which include conductive fillers such as graphene and carbon www.advelectronicmat.de [7,8] Specially, conductive cellulose inks which include conductive fillers such as graphene and carbon www.advelectronicmat.de…”
Section: Electrochemical Sensorsmentioning
confidence: 99%
“…[1][2][3] Representative sustainable nanocellulose materials like cellulose nanofibers (CNFs) and cellulose nanocrystals (CNCs) have been used as primary constituent materials for additive manufacturing. [7,8] Specially, conductive cellulose inks which include conductive fillers such as graphene and carbon www.advelectronicmat.de [7,8] Specially, conductive cellulose inks which include conductive fillers such as graphene and carbon www.advelectronicmat.de…”
Section: Electrochemical Sensorsmentioning
confidence: 99%
“…They found that the CNC particles align along the printing direction by shear flow, and the CNC inks display shear-thinning behavior. 32 Hence, CNC is a suitable additive for enhancing the shear-thinning property of bioink.…”
Section: -13mentioning
confidence: 99%
“…It is fabricated by mechanical or chemical treatment of cellulose resources. CNF has been considered for many potential applications such as oil industry, composite fabrication, coating, drug delivery, 3D printing inks, smart materials and so on [1][2][3][4] . CNF is isolated from many different cellulose sources such as wood and non-wood materials 5 .…”
Section: Introductionmentioning
confidence: 99%